Clase y género entre el espacio público y privado. Un análisis de la revista Para Ti en tiempos de crisis - Farías, Mónica (Universidad Nacional del Litoral, 2020)
This article presents a feminist analysis of the relationship between mass media and identities in times of structural change. Its goal is to fill the existing gap in the literature about the socioeconomic and political crisis of 2001-2002 in Argentina in relation to middle class media and the media. It conducts a discourse analysis of the magazine Para Ti between 1995 and 2008 and it pays attention to the magazine’s representations of 1) the relation between women, public space and politics, and 2) food consumption. I show how, in spite of some adjustments to the socioeconomic and political changes, women’s representations continued to be rooted in traditional models of femininity and domesticity. Thus, the magazine reinforced ‘class’ as a fundamental category of identity.